2001
DOI: 10.2307/3094874
|View full text |Cite
|
Sign up to set email alerts
|

Images in Words: Presidential Rhetoric, Charisma, and Greatness

Abstract: We are indebted to Daniel K. Brass and three anonymous reviewers for their guidance during the editorial process and to a host of colleagues for their feedback, conversations, and encouragement over the course of this project. Send correspondence to Cindy Emrich, Krannert Graduate School of Management, Purdue University, 1310 Krannert Building, West Lafayette, IN 47907-131 0; e-mail: cindy~mgmt.purdue.edu.We analyzed two sets of U.S. presidents' speeches to determine whether their propensities to convey images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
229
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(244 citation statements)
references
References 40 publications
12
229
0
3
Order By: Relevance
“…To date, no one has attempted to develop a conceptual framework of leadership and followers' emotional states (McColl-Kennedy & Anderson, 2002). This is surprising because many of the new theories of leadership such as charismatic and transformational leadership emphasize the emotional attachment of followers to the leader (Bass, 1985, Emrich et al, 2001and Gardner & Avolio, 1998. For example, House, Woycke, and Fodor (1988) argued that what differentiates charismatic from non-charismatic leaders is that charismatic leaders have their major effects on the emotions and selfesteem of followers, as opposed to non-charismatic leaders, whose primary effects are exerted on followers' cognitions and abilities.…”
Section: Emotionsmentioning
confidence: 99%
“…To date, no one has attempted to develop a conceptual framework of leadership and followers' emotional states (McColl-Kennedy & Anderson, 2002). This is surprising because many of the new theories of leadership such as charismatic and transformational leadership emphasize the emotional attachment of followers to the leader (Bass, 1985, Emrich et al, 2001and Gardner & Avolio, 1998. For example, House, Woycke, and Fodor (1988) argued that what differentiates charismatic from non-charismatic leaders is that charismatic leaders have their major effects on the emotions and selfesteem of followers, as opposed to non-charismatic leaders, whose primary effects are exerted on followers' cognitions and abilities.…”
Section: Emotionsmentioning
confidence: 99%
“…These specific linguistic components contribute to the acceptance and adoption of ideas as well as the likelihood of the concepts being distributed to others by stakeholders. These qualities have been used to explain the effectiveness of national health-care communication campaigns (Greenhalgh, Robert, Macfarlane, Bate, & Kyriakidou, 2004;Haider & Kreps, 2004), public policy programs (McLendon, Heller, & Young 2005;Valente, 1993), crisis management (Bligh, Kohles, & Meindl, 2004), political persuasion (Emrich, Brower, Feldman, & Garland, 2001;Holladay & Coombs, 1994), and business and marketing strategies (Mahajan, Muller, & Bass, 1990;Sevcik, 2004).…”
Section: The Verbiage Of Institutional Visionmentioning
confidence: 99%
“…We argue that a person's vocal attractiveness is a relevant aspect of the leader prototype. Previous research on leaders' communication has shown that the use of images conveyed in words strongly influences follower perceptions (Emrich, Brower, Feldman, & Garland 2001) and that the manner in which images are conveyed in political speeches can have impacts on attributions of leadership quality through follower reactions such as trust in the leader (Conger, Kanungo, & Menon 2000). However, to the best of our knowledge, no research has investigated the effects of vocal attractiveness on perceptions of leadership effectiveness.…”
mentioning
confidence: 67%